Interactions of a low molecular weight inhibitor from streptomyces sp. MBR04 with human cathepsin D: implications in mechanism of inactivation - Menon, Vishnu; Rao, Mala (Applied Biochemistry and Biotechnology, 2014)
Cathepsin D, a lysosomal aspartic protease, is of potential interest as a target for drug design due to its implication in breast and ovarian cancer. The article reports a low molecular weight cathepsin D inhibitor from Streptomyces sp. MBR04. The M-r of the inhibitor was 1,078 Da as determined by MALDI-TOF, and the amino acid analysis showed the presence of Asp, Asp, Gly, Ala, Lys, Leu, Tyr, Trp residues. The steady-state kinetic interactions revealed reversible, competitive, slow-tight-binding nature of the inhibitor with an IC50 and K (i) values of 3.2 and 2.5 nM, respectively. The binding of the inhibitor with the enzyme and the subsequent conformational changes were monitored by exploiting the intrinsic fluorescence of the surface exposed Trp-54 residue. Based on the fluorescence and circular dichroism studies, we demonstrate that the inhibitor binds to the active site of cathepsin D and causes inactivation. All these kinetic, thermodynamic, and quenching studies suggest that the newly isolated peptidic inhibitor could be a potential scaffold to study and can be used to develop new potent therapeutic lead molecule for the development of drugs. The inhibitor will be significant as a potential lead molecule to target cathepsin D.
Keywords: Cancer treatment; Cathepsin D inhibitor; Inactivation mechanism; Slow-tight-binding inhibition; Streptomyces sp MBR04